2020
DOI: 10.1038/s41598-020-72076-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic study of attenuation of monosodium glutamate mixed high lipid diet induced systemic damage in rats by Coccinia grandis

Abstract: In the context of failure of treatment for non alcoholic fatty liver disease (NAFLD)-mediated systemic damages, recognition of novel and successful characteristic drug to combat these anomalous situations is earnestly required. The present study is aimed to evaluate protective value of ethanol extract of Coccinia grandis leaves (EECGL), naturally occurring medicinal plant, on NAFLD-mediated systemic damage induced by high lipid diet along with monosodium glutamate (HM)-fed rats. Our study uncovered that EECGL … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 68 publications
10
62
0
Order By: Relevance
“…Additionally, MSG has been directly associated with nociceptive responses such as temporomandibular joint (TMJ) syndrome, musculoskeletal pain [ 11 ], etc. Furthermore, MSG also acts as a pseudo-allergic chemical that ultimately leads to Chinese restaurant syndrome and exerts inflammatory responses in the human body [ 35 , 46 , 14 ].…”
Section: Msg Used As a Flavor-enhancing Agent Causes Systemic Anomaliesmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, MSG has been directly associated with nociceptive responses such as temporomandibular joint (TMJ) syndrome, musculoskeletal pain [ 11 ], etc. Furthermore, MSG also acts as a pseudo-allergic chemical that ultimately leads to Chinese restaurant syndrome and exerts inflammatory responses in the human body [ 35 , 46 , 14 ].…”
Section: Msg Used As a Flavor-enhancing Agent Causes Systemic Anomaliesmentioning
confidence: 99%
“…Further investigation on cultural factors induced rapidly increasing NR-NCD can only give insight into some of the world's most unfavorable problems [ 278 ]. A recent study by Banerjee et al (2020) suggested that MSG mixed HLD caused NAFLD mediated systemic damage via generation of ROS with altered redox-homeostasis and pro-inflammatory/anti-inflammatory factors, which ultimately leads to apoptosis possibly through p53/p21 and mitochondrial caspase-mediated signaling [ 14 ]. A recent report proposed that flavor enhancing diet generates ROS and alters the redox homeostasis that indirectly stimulate the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) mediated infection causes novel coronavirus (COVID-19) outbreaks [ 294 ].…”
Section: Alarming Impact Of Savory Tastant In Hld On Human Healthmentioning
confidence: 99%
See 2 more Smart Citations
“… 3 However, coronavirus infection alters the redox-status by generating reactive oxygen species (ROS) followed by oxidative stress (OS) by manipulating host cell machinery, which causes different abnormal situations in the human body. 4 , 5 Moreover, regular consumption of a high-lipid diet alone or monosodium glutamate also disturbs the redox-equilibrium; 6 , 7 so it can hypothesize that such types of diets cause OS, which may indirectly stimulate the viral infection. Therefore, it can predict that OS plays a pivotal role in SARS-CoV-2 disorders that alter redox signaling to increase the severe acute respiratory syndrome risk.…”
Section: Introductionmentioning
confidence: 99%